The Effect of Tax Minimization and Exchange Rate on Transfer Pricing Decisions with Leverage as Moderating - Devi, Diah Kumala; Suryarini, Trisni (Accounting Analysis Journal, 2020)
The aims of this research are to analyze and to find empirical evidence about the effect of tax minimization and exchange rate on company decision of transfer pricing with leverage as moderating variable. The population of this research was mining companies which listed in Indonesia Stock Exchange (IDX) over the period 2013 to 2018 from 45 companies. The sampling technique used purposive sampling. Eighteen companies were selected with 65 units analysis were obtained. In addition, data was analyzed using descriptive statistics and inferential statistics using Moderated Regression Analysis (MRA). The data was processed by IBM SPSS Statistics 21 software. The results show that tax minimization and exchange rate have positive and significant effect on transfer pricing. Leverage does not moderate the effect of tax minimization on transfer pricing but leverage significantly moderate the effect of exchange rate on transfer pricing. The conclusion of this research is transfer pricing decision will be higher when tax minimization and exchange rate be higher, but leverage can moderate the effect of exchange rate to transfer pricing.